2017
DOI: 10.18632/oncotarget.23426
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-based chemotherapy as a viable option for treatment of advanced breast cancer patients: a meta-analysis and literature review

Abstract: This meta-analysis was designed to compare the efficacy and safety of gemcitabine-based regimens for the treatment advanced breast cancer (ABC). Altogether 15 studies involving 8195 ABC patients were retrieved for analysis. Compared with non-gemcitabine-based chemotherapies, patients receiving gemcitabine-based therapy exhibited better overall survival (OS), progression free survival (PFS), and objective response rate (ORR) (HR = 1.12, 95% CI 1.05 to 1.19; HR = 1.16, 95% CI 1.03 to 1.30; HR = 1.14, 95% CI 1.04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…25 This agent has proven antitumor activity and tolerability in various malignancies, including breast cancer. 26 Gemcitabine monotherapy has led to response rates of 37% in the rstline setting, 26% in the second-line setting, and 18% in the third-line setting. 25 Although Gemcitabine has been studied extensively in the phase II setting, it appears to have no particular advantage over existing chemotherapeutic agents in the third-line or greater setting.…”
Section: Discussionmentioning
confidence: 99%
“…25 This agent has proven antitumor activity and tolerability in various malignancies, including breast cancer. 26 Gemcitabine monotherapy has led to response rates of 37% in the rstline setting, 26% in the second-line setting, and 18% in the third-line setting. 25 Although Gemcitabine has been studied extensively in the phase II setting, it appears to have no particular advantage over existing chemotherapeutic agents in the third-line or greater setting.…”
Section: Discussionmentioning
confidence: 99%
“…Besides factors above, epigenetic mutations are also important factors in the tumorigenesis of BC 6 . Therefore, it is critical to identify the molecular mechanisms involved in the proliferation and progression genesis in BC [7][8][9] . Moreover, more valuable coping strategies and precise targeting therapies are pressing challenges with significant clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Controversial outcomes were retrieved from studies that evaluated the benefit of adding gemcitabine to treatment regimens or using it as a single agent in advanced BC. One recent metanalysis indicated that using gemcitabine in combination therapies demonstrated favorable outcomes in advanced, however, with considerable associated hematological toxicity (Xie et al, 2018).…”
Section: Gemcitabinementioning
confidence: 99%